PERUMUSAN STRATEGI BISNIS BERDASARKAN ANALISIS KEPUASAN KONSUMEN TERHADAP USAHA WARALABA - Sofiyanurriyanti Sofiyanurriyanti; T.M Azis Pandria (Jurnal Optimalisasi, 2019)
Indomaret is a company engaged in the largest retail business in Indonesia. Over time, Indomaret continued to add outlets in various areas of housing, offices, commerce, tourism and apartments. One of the outlets is located in Sidayu, Gresik Regency. In this case there is a learning process for the operation of a large-scale retail network. Promotional strategies are needed to outperform competition in the era of globalization. Data collection is done by identifying factors that influence the surrounding environment. The analysis model used in this study is the SWOT analysis and the Grand Strategy Matrix. This analysis is based on strengths, weaknesses, opportunities and threats. The results of this study indicate that the evaluation of the Indomaret franchise company the strategy that must be done to increase consumers is to continue to innovate that combines technology with market demand, namely shopping online. Whether it's in the form of transactions of goods or services online or with non-online ones. Indomaret is able to create innovations that are able to meet every customer's needs by making it easy to shop through the application. Indomaret is also able to see job opportunities by making innovations in the field of services, namely online couriers by utilizing the location of stores in various regions. As per the company motto, "easy and economical". Based on the calculation of internal and external factors, it can be seen that the factors of strength and weakness in the axis (X) are 0.352, while opportunities and threats are on the axis (Y) with a value of 0.354 in quadrant I which is a Growth Strategy where the strategy must be done evaluation, namely market development, market penetration, product development, future integration, backward integration, horizontal integration, and diversification.